Evidence of histopathological appearances in representative fishes and invertebrates from Libong Island, Thailand - Wikit Phinrub; Nisreen Dahlan; Sinlapachai Senarat; Atsuo lida; Natthawut Charoenphon; Narit Thaochan; Kitipong Angsujinda; Supapong Imsonpang (Veterinary Integrative Sciences)
The seagrass beds at Libong Island, Thailand, are a complex ecological habitat supporting many marine organisms. Unfortunately, the seagrass area is being lost, possibly exerting adverse impacts on aquatic life, but comprehensive aquatic monitoring and assessment efforts are still lacking. In this study, sentinel species were selected from two species groups commonly found in this area, pelagic species (Ambassis nalua and A. vachelli) and benthic species (Amphibalanus amphitrite, and Alpheus sp.). Specimens were collected from healthy and unhealthy seagrass areas around the island from April to June 2021. The health of the specimens was assessed using the histopathological approach together with the histological alteration index (HAI). Some histological alterations were identified that HAl values indicated were significantly more prevalent in the unhealthy seagrass areas (P<0.05). Among the invertebrates, A. amphitrite exhibited melanomacrophage centers while Alpheus sp. exhibited lamellar disorganization in gill and degeneration of hepatopancreatic cells. The two fish species exhibited vacuolar degeneration in the liver that was more pronounced in specimens from the unhealthy seagrass area. However, the HAI values calculated for all samples ranged from 0.1 to 1, indicating normal organs. These results suggest the emergence of environmental alteration in the threatened seagrass habitats at Libong Island, where there is a need to monitor impacts on flora and fauna health in further studies. It is also noted that fishes can be sensitive sentinel species of aquatic ecosystem health.